1)-15.4-3.(2x+12)=15.(-3) 2)-32-4x+15=-10+21 3)-(-3x).3 mũ 2=-15+(-12) 4)5-(-17-3)=x-(2-15) Tìm x 17/10/2021 Bởi Adalyn 1)-15.4-3.(2x+12)=15.(-3) 2)-32-4x+15=-10+21 3)-(-3x).3 mũ 2=-15+(-12) 4)5-(-17-3)=x-(2-15) Tìm x
`1)` : `-15 . 4 – 3(2x + 12) = 15 . (-3)` `-60 – 6x + 36 = -45` `-6x = -45 – 36 + 60` `-6x= -21` `x = 21/6 = 7/2` `2)` `-32 – 4x +15 = -10 +21` `-17 + 4x = -10+21` `4x =28` `x = 7` `3)` `-(-3x) . 3^2 = -15 – 12` ` 3x . 9 = -27` `3x = -3` `x = -1` `4)` `-5 – (-17 -3) = x – (2 – 15)` ` -5 + 17 + 3= x + 13` `x =2` Bình luận
`1) -15.4-3.(2x+12)= 15.(-3)` `-15.4-3.(2x+12)= -45` `4-3.(2x+12)= -45:(-15)` `4-3.(2x+12)= 3` `3.(2x+12)= 4-3` `3.(2x+12)= 1` `2x+12= 1/3` `2x= -35/3` `x= -35/6` `2) -32-4x+15= -10+21` `-32-4x+15= 11` `-32-4x= -4` `4x= -32-(-4)` `4x= -28` `x= -7` `3) -(-3x).3^2= -15+(-12)` `3x.9= -27` `3x= -3` `x= -1` `4) 5-(-17-3)= x-(2-15)` `x-(2-15)= x+13` `5^2= x+13` `25= x+13` `-x= -12` `=> x= 12` Bình luận
`1)` :
`-15 . 4 – 3(2x + 12) = 15 . (-3)`
`-60 – 6x + 36 = -45`
`-6x = -45 – 36 + 60`
`-6x= -21`
`x = 21/6 = 7/2`
`2)`
`-32 – 4x +15 = -10 +21`
`-17 + 4x = -10+21`
`4x =28`
`x = 7`
`3)`
`-(-3x) . 3^2 = -15 – 12`
` 3x . 9 = -27`
`3x = -3`
`x = -1`
`4)`
`-5 – (-17 -3) = x – (2 – 15)`
` -5 + 17 + 3= x + 13`
`x =2`
`1) -15.4-3.(2x+12)= 15.(-3)`
`-15.4-3.(2x+12)= -45`
`4-3.(2x+12)= -45:(-15)`
`4-3.(2x+12)= 3`
`3.(2x+12)= 4-3`
`3.(2x+12)= 1`
`2x+12= 1/3`
`2x= -35/3`
`x= -35/6`
`2) -32-4x+15= -10+21`
`-32-4x+15= 11`
`-32-4x= -4`
`4x= -32-(-4)`
`4x= -28`
`x= -7`
`3) -(-3x).3^2= -15+(-12)`
`3x.9= -27`
`3x= -3`
`x= -1`
`4) 5-(-17-3)= x-(2-15)`
`x-(2-15)= x+13`
`5^2= x+13`
`25= x+13`
`-x= -12`
`=> x= 12`